INFLUENCE OF PEPTIDE P34 ON GENE EXPRESSION OF LISTERIA MONOCYTOGENES AND LISTERIA SEELEGERI - Vaucher, Rodrigo De Almeida; Giongo, Janice Luehring; Estivales, Magton; Rech, Virgínia Cielo; Nishihira, Vivian Shinobu Kishimoto; Luchese, Cristiane; Wilhelm, Ethel Antunes; Baldissera, Matheus DellamÉa; Lopes, Leonardo Quintana Soares; Santos, Roberto Christ Vianna; Brandelli, Adriano (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Investigate the influence of the antimicrobial peptides P34 and nisin on the expression of genes associated with components of the cell surface of Listeria monocytogenes and Listeria seeligeri. Methods: Antimicrobial activity was determined by addition of peptide P34 and nisin (12.5 µg/ml) onto Brain Heart Infusion agar (BHI) plates previously inoculated with indicator strains (L. monocytogenes ATCC 7644 or L. seeligeri AC 82/4) after incubation for 24 h at 37 °C or 240 h at 4 °C. Ribonucleic acid (RNA) was directly extracted from bacterial colonies at the border of the inhibition zones, and the expression levels of genes D-alanine-D-alanyl carrier protein ligase (dltA), putative phospholipid lysinylation (Imo 1695) and EIIABMan of mannose-specific PTS (mptA) were determined using real-time PCR. Results: A non-significant increase in the levels of transcription of genes dltA, Imo1695 and mptA was observed for L. monocytogenes treated with peptide P34 or nisin. Both peptides caused a similar decrease in dltA gene expression in L. seeligeri. The expression of gene Imo1695 significantly decreased (about 2000-fold) after treatment with the peptide P34 at 37 °C, while at 4 °C a reduction of 12-fold and 5-fold was detected for P34 and nisin, respectively. A significant decrease in mptA gene expression was observed by exposition to peptide P34 (31.872-fold) and nisin (16.047-fold) for 24 h at 37 °C. Conclusion: The results suggest that both peptide P34 and nisin influence the expression of genes related with the cell-surface/cell-membrane structure of L. seeligeri and in lesser extent L. monocytogenes.